Increasing the Competitiveness of MSMEs in Depok City Through Digital Marketing, Financial Technology, and Artificial Intelligence - Lesmana, Rosa; Tatariyanto, Firman; Syahnego, Syahnego (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2025)
The purpose of this study is to determine the partial and simultaneous effects of the variables digital marketing, financial technology and artificial intelligence on improving the competitiveness of MSMEs in Depok City. This study employs a quantitative approach. The object of analysis consists of 190 MSME actors in Depok City. Data were collected through questionnaires. The analysis method uses SEM, and the analytical tool is LISREL version 8.80. The results indicate that, partially, the digital marketing variable does not have a positive and significant effect on improving the competitiveness of MSMEs in Depok City, and the same applies to the financial technology variable. However, artificial intelligence has a positive and significant effect on the competitiveness of MSMEs in Depok City. Simultaneously, digital marketing, financial technology and artificial intelligence have a positive and significant influence on increasing the competitiveness of MSMEs in the city of Depok.